The Importance of EFL Teaching in Hindu Gurukula Modern System - Si Luh Nyoman Seriadi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Education is a significant factor in building civilization. A civilization or a country will advance rapidly when its education system gives such a significant contribution to the development of Human Resources. The advancement of a nation determined by the extent of the educational institution which has succeeded in building its human being into a superior human being to be a dignified world citizen. Hindu civilization dramatically emphasizes the importance of education. In the history of Sanatana Dharma, training gets an enormous portion along with the building of the concept of gurukula, where teachers and sisya are living together in an educational institution. Moreover, when the West has not found an established educational system, India has built the world's earliest university Thaksashila or Taxila with a highly developed teaching system. But the progress of civilization in the past has not always been well inherited in the next era. Currently, Hindus, especially in Indonesia, are faced with Hindu-based education that can answer global challenges. Not only prosecuted to build superior human resources but educational institutions required to master technology as a worldwide phenomenon. Hindu educational institutions were requested to be capable of becoming a modern gurukula as well as capable of realizing superior human resources. Therefore, to answer the requirements of global challenges, students in gurukula must be able to overcome the language barrier. They have to be able to communicate well in English. Hence, the EFL(English as Foreign Language) Teaching becomes an essential part of the Hindu Gurukula Modern system.